2021
DOI: 10.1186/s13321-021-00570-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical toxicity prediction based on semi-supervised learning and graph convolutional neural network

Abstract: As safety is one of the most important properties of drugs, chemical toxicology prediction has received increasing attentions in the drug discovery research. Traditionally, researchers rely on in vitro and in vivo experiments to test the toxicity of chemical compounds. However, not only are these experiments time consuming and costly, but experiments that involve animal testing are increasingly subject to ethical concerns. While traditional machine learning (ML) methods have been used in the field with some su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…218 To address the lack of annotated toxicity data, they proposed using semisupervised learning algorithms, such as the Mean Teacher semisupervised learning algorithm, in combination with GCN. 218 Using Tox21 data, the authors found that the semisupervised learning-GCN models outperformed the GCN models trained by supervised learning and conventional machine-learning methods by 6% on 12 toxicological end points, achieving an average AUROC score of 0.757 in the test set. 218 They also found that unlabeled data was advantageous for model training, and the optimal unannotated to annotated data ratio ranged from 1:1 to 4:1.…”
Section: Gnnmentioning
confidence: 99%
See 2 more Smart Citations
“…218 To address the lack of annotated toxicity data, they proposed using semisupervised learning algorithms, such as the Mean Teacher semisupervised learning algorithm, in combination with GCN. 218 Using Tox21 data, the authors found that the semisupervised learning-GCN models outperformed the GCN models trained by supervised learning and conventional machine-learning methods by 6% on 12 toxicological end points, achieving an average AUROC score of 0.757 in the test set. 218 They also found that unlabeled data was advantageous for model training, and the optimal unannotated to annotated data ratio ranged from 1:1 to 4:1.…”
Section: Gnnmentioning
confidence: 99%
“…218 Using Tox21 data, the authors found that the semisupervised learning-GCN models outperformed the GCN models trained by supervised learning and conventional machine-learning methods by 6% on 12 toxicological end points, achieving an average AUROC score of 0.757 in the test set. 218 They also found that unlabeled data was advantageous for model training, and the optimal unannotated to annotated data ratio ranged from 1:1 to 4:1. 218 The study demonstrates the success of semisupervised learning in chemical toxicity prediction and suggests potential applications in other chemical property prediction tasks.…”
Section: Gnnmentioning
confidence: 99%
See 1 more Smart Citation
“…GCN is already well applied to predicting the compound property, and molecular fingerprint (Kojima et al, 2020;J. Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Graph Convolutional Network (GCN) is a kind of deep learning that can use nodes to contain feature information and edges to contain spatial information between nodes, which is a popular method in prediction relationships(S. Zhang et al ., 2019). GCN is already well applied to predicting the compound property, and molecular fingerprint(Kojima et al ., 2020; J. Chen et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%